Accord on “Fire and Building Safety in Bangladesh”: A Breakthrough Agreement? - Rahman, Zillur (Nordic Journal of Working Life Studies, 2014)
This discussion aims to review the emergence of the “Accord on Fire and Building Safety in Bangladesh” signed on May 13, 2013, and evaluate if it is an international agreement “breakthrough”. The Accord is signed not only by the global clothing brands and national garment unions but also by international trade union organizations, which is a new development. This raises a question: could this agreement set a new international negotiating precedence in industrial relations between transnational corporations and international trade union organizations? In Bangladesh, globalization has played an important role for booming garment industries. Yet, lack of workers’ rights, weak safety situations, and poor working conditions have continuously been reported. Local and international solidarity movements and garment workers’ welfare associations have been emphasizing workers’ rights and better and safer working environments in workplaces since the beginning of the 1990s. However, their voices were not highly considered even there were some initiatives. Following the ‘Rana Plaza’ garment factory building collapse in April 2013, one of the world’s worst industrial accidents, with more than 1,100 dead workers, some strong measures have been taken—one of these, signing the ‘Accord on Fire and Building Safety in Bangladesh’. This is a strong achievement of a long struggle to take collective action for improving the safety in garment factories in Bangladesh. Although the Accord is understood as a game changer or breakthrough in relation to national and international agreements, do we really know yet if it is a breakthrough or not when it comes to its implementation?